Comment le secteur logistique espagnol parvient-il à dépasser ses faiblesses structurelles et à consolider ses stratégies de sortie de crise ? - Gaëlle Fauchard (Cahiers de Civilisation Espagnole Contemporaine)
This article describes how the Spanish State and municipalities have developed their spatial planning practices and policies to implement European directives regarding environmental aspects on the one hand and promoting economic development of the regions on the other hand. A description of the mechanisms increasingly affecting the Spanish economy since the 1990s, justifies to shed light on corporate know-how implemented by companies specializing in transport and logistics to deal with the global crisis of 2008, despite the structural weaknesses of this sector. Lastly, an analysis of the main levers to lift economy will enable us to explain the main factors that have been boosting the activity of this sector since 2013. This economic dynamism is crucial for the country that tries to become a strategic European platform of the South for international exchanges.